Association between lipoprotein(a) and insulin resistance in Chinese adults: results from the China health and nutrition survey - Wang, Heng; Fan, Jia-Li (Frontiers in Endocrinology, 2023)
Background: Lipoprotein(a) [Lp(a)] is a well-established risk factor for cardiovascular diseases. However, the relationship between Lp(a) and insulin resistance (IR) remains controversial. The aim of the current study was to investigate the association between Lp(a) concentrations and IR in Chinese adults. Methods: Cross-sectional study of 1908 cases and 5725 controls was performed for identifying the association of Lp(a) with IR. IR was assessed using the TyG index, and patients with a TyG index greater than the third quartile were defined as having IR. Results: The distribution of Lp(a) in Chinese adults was skewed, with a median of 7.90mg/dL. Lp(a) concentrations were significantly and progressively lower with increasing TyG index values in Chinese adult males, but not in females. Multiple regression analysis adjusted for a wide range of risk factors showed that Lp(a) concentrations were inversely and independently associated with IR in Chinese adult males, but not in females. The suggested Lp (a) cutoff for discriminating IR from non-IR was 4.7 mg/dL in Chinese adult males. Lp(a) interacts with gender in IR on both additive and multiplicative scale in Chinese adults. Conclusion: Lp(a) concentrations inversely associated with IR in Chinses adult males, but the association in women needs further study. In Chinese adults , Lp(a) interacts with gender in IR.